1990
DOI: 10.1139/x90-059
|View full text |Cite
|
Sign up to set email alerts
|

Physiological processes in plantation establishment and the development of specifications for forest planting stock

Abstract: Both the morphological and physiological characteristics of forest planting stock vary widely with nursery culture and environment. Through the control of environmentally determined variation in phenotype, stock can be adapted to both the stress of transplanting from nursery to forest site and the particular environmental conditions of the forest site. Evidence is discussed that indicates that the stress of transplanting is primarily water stress, resulting from (i) the confinement of roots to the planting hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
228
1
41

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(282 citation statements)
references
References 0 publications
12
228
1
41
Order By: Relevance
“…Shoot development, as described by Krutzsch index and growth of the 1998-seedlings during the first 1.5 months indicated that there were little difference between treatments in seedling growth during the first period after planting. During this time, the seedlings were probably more restricted by stress of transplanting than by environmental constraints [5,21]. The length of the second-year leading shoot was shorter than the first-year leading shoot for all treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoot development, as described by Krutzsch index and growth of the 1998-seedlings during the first 1.5 months indicated that there were little difference between treatments in seedling growth during the first period after planting. During this time, the seedlings were probably more restricted by stress of transplanting than by environmental constraints [5,21]. The length of the second-year leading shoot was shorter than the first-year leading shoot for all treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Water availability in the soil may be a limiting factor during dry years and competition for water from field vegetation may therefore cause mortality among newly planted seedlings [5,13]. Competition for water varies however significantly between regions.…”
Section: Introductionmentioning
confidence: 99%
“…Although height growth was restricted after budset [33], shoot dry mass increased by 89 to 122% (figure 2) attributed mainly to thickening of the stem and cell walls, and lignification of secondary xylem [7,8]. The late-season reallocation of biomass to roots may also contribute to enhanced outplanting performance because increased root size at planting is often beneficial for subsequent water and nutrient uptake [6,24,30].…”
Section: Growth and Biomass Partitioningmentioning
confidence: 99%
“…Water stress, which can be caused by limited contact between roots and soil, low hydraulic conductance of suberized roots and/or root confinement, represents the main constraint for plant survival and growth [3,12,35].…”
Section: Introductionmentioning
confidence: 99%